Immersion enthalpy variation of surface-modified mineral activated carbon in lead (II) aqueous solution adsorption: the relation between immersion enthalpy and adsorption capacity - Gutierrez, Liliana Giraldo; Moreno-Piraján, Juan Carlos (Eclética Química, 2006)
An activated carbon was obtained by chemical activation with phosphoric acid, CM, from a mineral carbon. Afterwards, the carbon was modified with 2 and 5 molL -1 , CMox2 and CMox5 nitric acid solutions to increase the surface acid group contents. Immersion enthalpy at pH 4 values and Pb 2+ adsorption isotherms were determined by immersing activated carbons in aqueous solution. The surface area values of the adsorbents and total pore volume were approximately 560 m 2 .g -1 and 0.36 cm 3 g -1 , respectively. As regards chemical characteristics, activated carbons had higher acid sites content, 0.92-2.42 meq g -1 , than basic sites, 0.63-0.12 meq g -1 . pH values were between 7.4 and 4.5 at the point of zero charge, pH PZC. The adsorbed quantity of Pb 2+ and the immersion enthalpy in solution of different pH values for CM activated carbon showed that the values are the highest for pH 4, 15.7 mgg -1 and 27.6 Jg -1 respectively. Pb 2+ adsorption isotherms and immersion enthalpy were determined for modified activated carbons and the highest values were obtained for the activated carbon that showed the highest content of total acid sites on the surface.